Metabolomics and Whole-Exome Sequencing in Patients with Differential Sensitivity to Sevoflurane: A Protocol for a Prospective Observational Trial - Yiyong Wei; Yiyong Wei; Donghang Zhang; Yunxia Zuo (Frontiers Media S.A., 2021)
Introduction: Different sensitivity to volatile anesthetics in Drosophila, nematodes and mice is related to mutation of energy metabolism genes. In clinical practice, we find that the end-tidal sevoflurane concentration (ETsevo) differs among patients at the same depth of anesthesia, indicating that the sensitivity to sevoflurane varies among patients. However, the underlying mechanism remains unclear. The sensitivity of an anesthetic is associated with the postoperative outcomes of patients and the mechanism of action of volatile anesthetics. We therefore propose this protocol to determine whether differences in metabolite profile and genetic variations contribute to patients' sensitivity to volatile anesthetics.Methods and Analysis: This is a single-centre, prospective observational study. 720 patients undergoing abdominal surgery were included. General anesthesia was induced with inhaled sevoflurane, a bolus of sufentanil (0.2-0.4 μg/kg) and cis-atracurium (0.2-0.3 mg/kg). The end-tidal sevoflurane concentration (ETsevo) was adjusted to maintain a BIS (bispectral index) value between 40-60. The mean ETsevo from 20 min after endotracheal intubation to 2 h after the beginning of surgery (steady state) was calculated for each patient. Patients were further divided into a high-sensitivity group (mean ETsevo - SD) and a low-sensitivity group (mean ETsevo + SD) to investigate the sensitivity to sevoflurane. Cases were paired from the high-sensitivity group (group H) and low-sensitivity group (group L) according to age, sex, body mass index (BMI), ASA physical status classification, vital signs, BIS, ephedrine use, sufentanildose, and cis-atracurium dose at anesthesia induction and steady state. Differences in metabolite levels, single nucleotide polymorphisms (SNPs) and protein-coding gene sequence variations between group H and group L will be determined through plasma metabolomics, whole-exome sequencing (WES), genome-wide association study (GWAS), and bioinformatics analyses. These results will be analysed to determine the reasons for the differential sensitivity to sevoflurane in humans.Ethics and Dissemination: This prospective observational study protocol has received ethical approval from the Ethical Committee of West China Hospital of Sichuan University on May 19, 2017 (Approval No. 78). Informed consent will be obtained before patient enrolment. The results will be submitted to international peer-review journals.Trial Registration Number: ChiCTR1800014327.